Aproveitamento de subprodutos da indústria de carne suína: caracterização físico-química do queijo de porco - Silva Junior, Jamil Correia da (2015)
Headcheese is a meat sausage originated from Europe made from hog slaughter by-products. It is a much appreciated product in the South of Brazil which is increasingly established in the market, however it does not have official regulations yet. This study aimed to present the physicochemical characterization of headcheese in a western Santa Catarina industry supervised by Companhia Integrada de Desenvolvimento Agrícola de Santa Catarina and assess 10 different brands to find the relationship between chemical composition and texture profile analysis (TPA). Thus, the chemical composition, energy value, total nitrite, lipid oxidation and physical parameters (color and texture) were evaluated. The product exhibited great variability in moisture content, lipid and protein because the different formulations, processing and intrinsic and extrinsic characteristics of raw material. The utilization of offal provided higher cholesterol and iron levels, and the high content of collagen was accountable for the shear force responses (7.84 ± 1.68 N). The product showed higher amount of sodium, due to the use of additives, but calcium levels were compatible with other sausages. There was a predominance of polyunsaturated fatty acids and polyunsaturated fatty acids/saturated fatty acids ratio was more favorable than other sausage in the same category. Nitrite assured preservation effects and thus lower product levels of oxidation were observed. The high Water Activity and pH 6.5 showed that the product is susceptible to growth of pathogens and requires cooling for preservation. Its brownish occurred due to cooking and production of metmyoglobin. There was a strong positive correlation between collagen and attributes of TPA, especially for chewiness (r = 0.855). The use of Hierarchical Cluster Analysis and Principal Component Analysis were able to separate three groups based on the amount of collagen and texture attributes, especially hardness, gumminess and chewiness.